Development of virtual reality framework in Malaysian automotive manufacturing industry - Mousavi, Maryam (2011)
Automotive industry is considered as initial group to use Virtual Reality (VR) technologies. VR provides new opportunity to improve productivity and enhances quality of manufacturing. Malaysian automotive industry also adopted VR and Three-Dimensional (3D) modelling at different stages. The industry mainly uses VR and 3D for production planning, prototyping, styling and designing, testing and manufacturing. Due to technological advancement, the industries are keen to adopt new technologies for its development. It is always difficult to choose the right technology at the right time and at the right place. There is no clear guideline among automotive industry about technological causes behind their success and failure. Most of the time, automotive industry is confused to choose which technology is most appropriate for their technology-based industrialization and improvement. However, without adopting advanced technology, the automotive industry cannot compete with its global competition. They need to choose the right technology for the right purpose. Users of technologies also need to select the appropriate technology according to the requirement of the industry. There is a gap in the selection process of technology, i.e. 3D, VR for the industry and who uses technology. In order to come-up with solutions to these problems, this research aims to reduce the mentioned technological gap and provides a guideline for choosing the appropriate technology for industrial development, and give a clear picture about the use of VR and 3D in vehicle manufacturing industry. It is important to conduct the research on VR and 3D used in industry to have a complete overview of the technology for the industrialists, researchers and developers. Six automotive companies in Malaysia were selected as case studies to develop future model of VR, which are namely Proton, Perodua, Toyota, Honda, Nissan and Naza. A total number of 240 questionnaires were distributed between these six automotive companies and 153 people responded to the questionnaires. Based on the questionnaires, this research analyses the existing VR systems, verifies VR adoption capability in automotive industry, identifies the opportunities of VR in the industry and its constraints, as well as develop a VR framework for automotive manufacturer industry in Malaysia. From the statistical analysis, it was found that 54% of respondents agreed and stated that the existing technology is not enough and also 83.7% respondent replied to adopt and improve new technology. Majority of the respondents showed common agreement (up to 60%) that VR can be appropriate to be adopted as an advanced technology in different sections of automotive manufacturing industry. Finally, the research provides a framework for automotive industry adoption with VR technology. This framework recommends the VR technology adoption to the automotive industry based on its remarkable points in each department of the industry. The framework will help policy makers, managers, designers, engineers, and researchers to make a decision more easily and efficiently for technology implementation in VR. The developed framework was validated using another set of questionnaire survey. Overall, it is supported by more than 90% of respondents that the framework is easily understood, feasible, applicable, comprehensive approach, which covers all major aspects of VR adoption in Malaysian automotive industry, and it provides a straightforward guidance even to beginners.